If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 10 + -1x = 4x + 19 Reorder the terms: 10 + 2x + -1x = 4x + 19 Combine like terms: 2x + -1x = 1x 10 + 1x = 4x + 19 Reorder the terms: 10 + 1x = 19 + 4x Solving 10 + 1x = 19 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 10 + 1x + -4x = 19 + 4x + -4x Combine like terms: 1x + -4x = -3x 10 + -3x = 19 + 4x + -4x Combine like terms: 4x + -4x = 0 10 + -3x = 19 + 0 10 + -3x = 19 Add '-10' to each side of the equation. 10 + -10 + -3x = 19 + -10 Combine like terms: 10 + -10 = 0 0 + -3x = 19 + -10 -3x = 19 + -10 Combine like terms: 19 + -10 = 9 -3x = 9 Divide each side by '-3'. x = -3 Simplifying x = -3
| x^2-44=-7x | | 5x-20x= | | X^2-12x=-18 | | -6+(-12)= | | 9z+16z=10+15 | | k^2-2k-35=0 | | x-18.33=.4239291x | | -7(t-6)-(t+1)=8 | | 7y-4=16+3y | | 7y-4=16 | | y+8-2y=3y+22 | | -5+-8= | | (2+8)x=200 | | x+0.20x=45 | | 4x-8x= | | 12=x+x+x | | 3(x-1)=2x-2(2x-1)+5 | | (2x+1)+5=53 | | 3(x-5)+(4-x)=8 | | (2x+1)2+5=53 | | 6(2+c)=5c+15 | | 8.2x+38.13=-11.8+36.57 | | 2+8(x-6)=7-3(x-9) | | 15x^2-23x-5=0 | | 9v^2+11v+4=0 | | 8c+6=5c+9 | | (4x+20)=(5x-2) | | 6x^2+12x+5=0 | | 4x+20=5x-2 | | 15x^2+38x+7=0 | | -6(t-4)-(t+5)=11 | | -2s^2+4s+16=0 |